(3GdCQHYhf MOjKkGs - (3eMeO Gdchaj , eMeO Hf Ydj Hf ejehf Hf eMeO GdfQSj, CHh GdZfGFe,J (B510 (3g` s
(3ChdgG (B:s
(3CNHQfG GdbGVi GdCLd TeS GdOjf LYaQ Hf CMeO Hf CHj jMji bGd GdTjN CHh GdZfGFe GdMeO ddg eHJOC GdMeO hefJgi GdeLO s
(3BNQgG (B:s
(3ef GdMOjK GdCQHYjf bhdg (B: (3hEf fYJ HeG QRbc Gddg , aCfJ CZfi GdfGS JeJ GdCMGOjK GdCQHYhf HMeO Gddg hefg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3cJHJ GdYfGhjf HGdMeQIs
(3eged GdfbW CMjGfkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B66s
Keywords: (3GdMOjK h GdeUWdMs